CUSTEQUITY scale: Measurement and validation in Indian banking sector - Hardeep Chahal; Renu Bala (Cogent Business & Management, 2017)
Purpose: This paper seeks to further the understanding of the domain of the customer equity construct, in developing country context. Building on their framework, a modified and extended construct (CUSTEQUITY), using systematic scale development procedure, is established with nomological evidence of its impact in Indian banking industry. Design/methodology/approach: The data are collected from 550 accountholders of five major national Indian banks–State Bank of India (SBI), Punjab National Bank (PNB), Housing Development Finance Corporation (HDFC), Industrial Credit and Industrial Corporation (ICICI), and Jammu and Kashmir Bank (JKB). The respondents are contacted using purposive sampling from Jammu city of North India. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation model (SEM) are used to analyze the data. Findings: The study findings validate the extended customer equity scale comprising two additional dimensions namely relational equity and social equity, along with three established dimensions-brand equity, value equity and retention equity. Further, the nomological validity of the CUSTEQUITY scale is also established. The moderating role of age and gender in customer equity and customer loyalty relationship is also supported. Also, the role of relationship length as a nomological moderator is established. Research limitations/implications: The study focuses on scale development on customer equity in Indian banking sector. The scale validity and reliability across the globe need to be established to underpin customer equity framework.
Keywords: 650